Tahfidzul Quran as a Moral Filter in Facing the Challenges of Artificial Intelligence in the Digital Era - Yaqin, Mukhamad Ainul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
The development of Artificial Intelligence (AI) in the digital era presents significant ethical challenges to human morality and character. The amoral operation of AI has contributed to the degradation of empathy and the spread of disinformation, leading to a crisis of spiritual values within society. This research employs a qualitative method with a literature review approach. A critical analysis was conducted to examine the role of tahfidzul Qur'an (Qur'an memorization) as a conceptual solution in facing the ethical challenges posed by AI and digitalization. The analysis indicates that tahfidzul Qur'an serves as an effective moral filter. This process is more than just a ritualistic memorization; it deeply instills Qur'anic values such as honesty, patience, and the importance of tabayyun (information verification). These values form an internal ethical fortress that equips individuals to engage with technology wisely and ethically. It is concluded that the most effective solution is not to reject technology but to integrate the spirituality offered by tahfidzul Qur'an with sound digital literacy. This combination can shape a generation that is not only technologically intelligent but also spiritually mature and morally upright, thus capable of utilizing AI for good. This finding provides a foundation for integrating Qur’anic ethics into digital literacy education.